AN UNKNOWN COMPONENT OF A SELECTIVE AND MILD OXIDANT: STRUCTURE AND OXIDATIVE ABILITY OF A DOUBLE SALT-TYPE COMPLEX HAVING κ1O-COORDINATED PERMANGANATE ANIONS AND THREE- AND FOUR-FOLD COORDINATED SILVER CATIONS - G.B. Kovács, N.V. May, P.A. Bombicz, S. Klábert, P. Németh, A. Menyhárd, G. Novodárszki, V. Petrusevski, F.P. Franguelli, J. Magyari, K. Béres, I.M. Szilágy, L. Kótai (RSC (Royal Society of Chemistry), 2019)
Compounds containing redox active permanganate anions and complexed silver cations with reducing pyridine ligands are used not only as selective and mild oxidants in organic chemistry but as precursors for nanocatalyst synthesis in low-temperature solid-phase quasi-intramolecular redox reactions. Here we show a novel compound (4Agpy2MnO4$Agpy4MnO4) that has unique structural features including (1) four coordinated and one non-coordinated permanganate anion, (2) k1O-permanganate coordinated Ag, (3) chain-like [Ag(py)2]+ units, (4) non-coordinated ionic permanganate ions and an [Ag(py)4]+ tetrahedra as well as (5) unsymmetrical hydrogen bonds between pyridine a-CHs and a permanganate oxygen. As a result of the oxidizing permanganate anion and reducing pyridine ligand, a highly exothermic reaction occurs at 85 C. If the decomposition heat is absorbed by alumina or oxidation-resistant organic solvents (the solvent absorbs the heat to evaporate), the decomposition reaction proceeds smoothly and safely. During heating of the solid material, pyridine is partly oxidized into carbon dioxide and water; the solid phase decomposition end product contains mainly metallic Ag, Mn3O4 and some encapsulated carbon dioxide. Surprisingly, the enigmatic carbon-dioxide is an intercalated gas instead of the expected chemisorbed carbonate form. The title compound is proved to be a mild and efficient oxidant toward benzyl alcohols with an almost quantitative yield of benzaldehydes.
–